A novel fluorescent sensor for diammonium and metal ions based on a supramolecular charge-transfer complex of bis(aza-18-crown-6)-containing dienone - Gromov, Sergey P.; Fomina, Marina V.; Zdorovenko, Ilia P.; Fakhrutdinov, Artem N.; Ushakov, Evgeny N. (Frontiers in Chemistry, 2023)
A bis(aza-18-crown-6)-containing 2,5-di(benzylidene)cyclopentanone and a bis(ammoniopropyl) derivative of 1,2-di(4-pyridyl)ethylene in MeCN were found to form a supramolecular charge-transfer complex, which can act as an "off–on" fluorescent sensor for the Ca2+ and 1,12-dodecanediammonium ions. The molecular structure of this complex in solution was studied by density functional theory calculations.